Association of dietary calcium intake, total and ionized serum calcium levels with preeclampsia in Ethiopia - Rahel D. Gebreyohannes; Ahmed Abdella; Wondimu Ayele; Ahizechukwu C. Eke (BMC, 2021)
Abstract Background Preeclampsia is a well-known cause of maternal mortality and morbidity in Ethiopia. The exact pathophysiology has not been fully understood. Calcium and magnesium deficiencies have been given emphasis to play roles in the pathophysiology. Although evidence is abundant, they are equivocal. The study aimed to see the association of dietary calcium intake, serum total calcium level and ionized calcium level with preeclampsia. It also evaluated the association between dietary calcium intake and serum calcium levels. Materials and methods An unmatched case-control study was conducted in Gandhi Memorial, Tikur Anbessa, and Zewditu Memorial Hospitals, all in Addis Ababa, between October to December, 2019. Cases were 42 women with preeclampsia and controls were 42 normotensive women. The medical and obstetric history was gathered using a structured questionnaire and the dietary calcium intake information using a 24-h dietary recall. The serum levels of total serum calcium and ionized (free) calcium were measured using an inductively coupled mass spectrophotometer. Bivariate and multivariate logistic regression and Pearson correlation test were utilized during data analysis. Results In comparison with controls, women with preeclampsia had lower mean (± 1SD) levels of ionized calcium level (1.1 mmol/l ± 0.11), total serum calcium level (1.99 mmol/l ± 0.35) and lower median (IQR) dietary calcium intake (704 mg/24 h,458-1183). The odds of having preeclampsia was almost eight times greater in those participants with low serum ionized calcium level (OR 7.5, 95% CI 2.388-23.608) and three times higher in those with low total serum calcium level (OR 3.0, 95% CI 1.024-9.370). Low dietary calcium intake also showed statistically significant association with preeclampsia (OR 3.4, 95% CI 1.092 -10.723). Serum ionized calcium level and total serum calcium level showed positive correlation of moderate strength (p = 0.004, r = 0.307), but no correlation was found between dietary calcium intake with both forms of serum calcium levels. Conclusion This study showed significant association between low dietary calcium intake and low serum calcium levels with preeclampsia, hence this can be used as a supportive local evidence for the current context-specific recommendation of calcium supplementation in societies with low-dietary calcium consumption in an attempt to prevent preeclampsia, therefore implementation study should be considered in Ethiopia to look for the feasibility of routine supplementation.